A Generalized System of Nonlinear Variational Inequalities in Banach Spaces - Prapairat Junlouchai; Anchalee Kaewcharoen; Somyot Plubtieng (Abstract and Applied Analysis, 2014)
We introduce a new generalized system of nonlinear variational inequality problems (GSNVIP) by using the generalized projection method. Moreover, we introduce an iterative scheme for finding a solution to this problem. Moreover, some existence and strong convergence theorems are established in uniformly smooth and strictly convex Banach spaces under suitable conditions. The results presented in the paper improve and extend some recent results.